ผลการใช้ชุดสื่อการเรียนรู้ดิจิทัลเพื่อส่งเสริมการรู้จำนวนสำหรับเด็กปฐมวัย - Foithong, Kunphatson; Butkatunyoo, Oraphan; Hirunchalothorn, Piyanan (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2024)
Effects of Digital Learning Sets for Promoting Numeracy of Young Children Kunphatson Foithong, Oraphan Butkatunyoo and Piyanan Hirunchalothorn รับบทความ: 20 พฤษภาคม 2567; แก้ไขบทความ: 26 กรกฎาคม 2567; ยอมรับตีพิมพ์: 28 กรกฎาคม 2567; ตีพิมพ์ออนไลน์: 24 ธันวาคม 2567 บทคัดย่อ การศึกษาวิจัยในครั้งนี้มีวัตถุประสงค์เพื่อเปรียบเทียบผลการใช้ชุดสื่อการเรียนรู้ดิจิทัลเพื่อส่งเสริมการรู้จำนวนสำหรับเด็กปฐมวัย กลุ่มเป้าหมายที่ใช้ในการศึกษาวิจัยในครั้งนี้ คือ เด็กปฐมวัยที่มีอายุ 5–6 ปี กำลังศึกษาอยู่ในระดับชั้นอนุบาล 3 ภาคเรียนที่ 2 ประจำปีการศึกษา 2566 โรงเรียนแห่งหนึ่งสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษานครปฐม เขต 2 จำนวน 13 คน เครื่องมือที่ใช้ในการศึกษาวิจัย ได้แก่ ชุดสื่อการเรียนรู้ดิจิทัลเพื่อส่งเสริมการรู้จำนวนสำหรับเด็กปฐมวัย จำนวน 8 ชุด และแบบประเมินการรู้จำนวนของเด็กปฐมวัย วิเคราะห์ข้อมูลเชิงปริมาณโดยใช้ค่าเฉลี่ย ค่าส่วนเบี่ยงเบนมาตรฐาน และวิเคราะห์ข้อมูลเชิงคุณภาพ โดยการวิเคราะห์เนื้อหา ผลการศึกษาพบว่าผลการใช้ชุดสื่อการเรียนรู้ดิจิทัลเพื่อส่งเสริมการรู้จำนวนของเด็กปฐมวัย มีคะแนนหลังการทดลองสูงกว่าก่อนการทดลอง ทั้งโดยรวมและรายด้านซึ่งการใช้ชุดสื่อการเรียนรู้ดิจิทัลสามารถพัฒนาการรู้จำนวนของเด็กปฐมวัย โดยเด็กสามารถเข้าใจเกี่ยวกับการสำรวจวัตถุ เข้าใจเกี่ยวกับการนับและบอกจำนวนวัตถุ เข้าใจเกี่ยวกับการมองภาพของวัตถุ เข้าใจเกี่ยวกับสัญลักษณ์แทนจำนวน เข้าใจเกี่ยวกับการแสดงวิธีการแก้ไขปัญหา วิธีการเหล่านี้สามารถเป็นแนวทางในการจัดกิจกรรมสำหรับครูหรือผู้ที่สนใจเกี่ยวกับการจัดกิจกรรมโดยใช้ชุดสื่อการเรียนรู้ดิจิทัล เพื่อส่งเสริมการรู้จำนวนให้เด็กปฐมวัย คำสำคัญ: การรู้จำนวน ชุดสื่อการเรียนรู้ดิจิทัล เด็กปฐมวัย Abstract The objective of this research was to compare the results of using digital learning media sets to promote numeracy for young children. The target group for this research study are 13 young children aged 5–6 years who are studying in the kindergarten level 3 in the second semester of the academic year 2023 at a school in Nakhon Pathom province, the Nakhon Pathom Primary Educational Service Area Office District 2. The tools used in the research include 8 sets of digital learning media to promote number literacy for young children and an assessment form of young children’s numeracy of young children.Quantitative data were analyzed using averages and standard deviation; qualitative data were analyzed by way of content analysis. The research findings showed that the use of digital learning media sets to promote numeracy among young children, both overall and in each aspect, yielded higher post–experiment scores than pre–experiment scores. The use of digital learning media sets can develop young children’s numeracy. Children were able to understand exploring objects, understand counting and telling the number of objects, understand the visualization of objects, understand symbols that represent numbers and understand how to display solutions. These methods can serve as guidelines for organizing activities for teachers or those who are interested in organizing activities using digital learning media sets to promote numeracy in young children. Keywords: Numeracy, Digital learning sets, Young children